Preliminary investigation of the vacuum pyrolysis of bituminous roofing waste materials. Issue 2 (1st March 2003) - Chaala, A; Roy, C
Abstract : The treatment of bituminous roofing waste materials by vacuum pyrolysis was tested in a pilot plant. The pyrolysis experiment was carried out batchwise at a temperature of 500°C and a total maximum pressure of 16 kPa. The amount of feedstock tested was 37 kg. Pyrolysis product yields were 52.3 wt.% oils, 31.2 wt.% solids, 14.4 wt.% pyrolysis gas, and 0.4 wt.% water. Losses were 1.7 wt.%. The pyrolysis oils have a gross calorific value of 42.7 MJ/kg and can be used as a heating fuel. The oil as a whole also represents a valuable material for petrochemical applications. The gas is rich in hydrocarbons and can be used as a make-up heat source (45.2 MJ/kg) for the thermal decomposition process. The solid residues exhibit a moderate calorific value of 17.5 MJ/kg and might find their way as a solid fuel in cement kilns. The nature of the minerals present in the solid residues, which amount to 49.7 wt.%, seems to be compatible with the cement composition. The vacuum pyrolysis technology is viewed as a potential solution to landfill and incineration of this waste construction material. Key words : construction, waste, shingles, bituminous, roofing, pyrolysis, fuels, environment, petrochemicals.